2015
DOI: 10.1111/fwb.12696
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐stage disruption of freshwater mussel reproduction by high suspended solids in short‐ and long‐term brooders

Abstract: Summary Suspended solids are one of the most widespread pollutants in streams, but little is known about their effects on freshwater mussels. In a previous study, we showed that increasing concentrations of total suspended solids (TSS) resulted in a decreased proportion of gravid female mussels; however, the generality of this effect and the specific stage at which reproduction was inhibited remain unknown. In this study, we examined stage‐specific disruption of reproduction in a short‐term brooding mussel s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Measured declines in mussel populations over the past century in many rivers across the U.S. have been attributed to a variety of causes, including increases in water velocity, shear stress and suspended sediment loads. These factors have been hypothesized to interfere with filtration, fertilization, recruitment and establishment of juvenile mussels in several studies (Reid et al, 2012;Gascho Landis et al, 2013;French & Ackerman, 2014;Gascho Landis & Stoeckel, 2016;Hansen et al, 2016;Stoeckel & Geist, 2016;Hornbach et al, 2019). However, our results suggest highsuspended sediment loads may not affect mussel glycogen content or growth in a negative way.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Measured declines in mussel populations over the past century in many rivers across the U.S. have been attributed to a variety of causes, including increases in water velocity, shear stress and suspended sediment loads. These factors have been hypothesized to interfere with filtration, fertilization, recruitment and establishment of juvenile mussels in several studies (Reid et al, 2012;Gascho Landis et al, 2013;French & Ackerman, 2014;Gascho Landis & Stoeckel, 2016;Hansen et al, 2016;Stoeckel & Geist, 2016;Hornbach et al, 2019). However, our results suggest highsuspended sediment loads may not affect mussel glycogen content or growth in a negative way.…”
Section: Discussionmentioning
confidence: 99%
“…Second, at high levels of suspended solids there could be negative impacts on the availability of sperm for reproduction leading to reduced reproduction. Gascho Landis & Stoeckel (2016) found that even when the organic matter content of suspended material was high there were negative impacts on reproduction in mussels. Thus, high food availability, which would support higher growth, coupled with high-suspended solids could still result in lower population sizes due to reproductive failure.…”
Section: Attributed Highermentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, decreases in water clarity impede photosynthetic organisms (Madsen, Chambers, James, Koch, & Westlake, ), and make food acquisition challenging for visual predators (Barkalow & Bonar, ; Swanbrow Becker, Brooks, & Gabor, ). Increased TSS has likely contributed to the decline of unionid mussels through reductions in feeding and reproductive efficiencies (Aldridge, Payne, & Miller, ; Gascho Landis & Stoeckel, ; Tuttle‐Raycraft et al., ) and disruption of unionid–host fish relationships (McNichols, Mackie, & Ackerman, ). Consequently, approximately 44% of unionid species globally, and more than 70% in North America, have conservation concerns (Hansen et al., ; Lopes‐Lima et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Contributing factors to the decline in unionid populations include overexploitation (Lopes-Lima et al 2017), invasive species (Lucy et al 2014), loss of fish hosts (McNichols et al 2011), loss of habitat, and habitat alteration (Poole and Downing 2004) including the negative impacts of increased total suspended solids (TSS; e.g., Gascho Landis et al 2013;Tuttle-Raycraft et al 2017) due largely to erosion (Brim Box and Mossa 1999;Santos et al 2015). Whereas certain mussel species are tolerant of turbid conditions and silt accumulation (Ellis 1936), large and diverse populations of other species are found in turbid rivers, where they are predicted to have lower feeding and reproductive efficiency (Gascho Landis and Stoeckel 2016;Tuttle-Raycraft et al 2017). Specifically, elevated TSS in turbid rivers should result in lower clearance rates (CR; volume of water cleared of particles per unit time; Widdows et al 1979) as TSS concentrations exceed 8-20 mg L −1 (Gascho Landis et al 2013;Tuttle-Raycraft et al 2017) because bivalves spend more time cleaning their gills (i.e., producing pseudofeces; Foster-Smith 1975).…”
mentioning
confidence: 99%